2015
DOI: 10.1073/pnas.1421063112
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 family member BOK promotes apoptosis in response to endoplasmic reticulum stress

Abstract: B-cell lymphoma 2 (BCL-2) ovarian killer (BOK) is a BCL-2 family protein with high homology to the multidomain proapoptotic proteins BAX and BAK, yet Bok−/− and even Bax−/−Bok−/− and Bak−/−Bok−/− mice were reported to have no overt phenotype or apoptotic defects in response to a host of classical stress stimuli. These surprising findings were interpreted to reflect functional compensation among the BAX, BAK, and BOK proteins. However, BOK cannot compensate for the severe apoptotic defects of Bax−/−Bak−/− mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 25 publications
4
128
2
Order By: Relevance
“…However, this hypothesis was not supported by the overwhelmingly strong apoptotic phenotype of Bax/Bak DKO cells (Wei et al 2001). Recent data from Bok knockout and Bax/ Bak/Bok triple-knockout cells further demonstrated that Bok's apoptotic activity is Bax/Bak-dependent and that it does not play a role as an effector protein during MOMP (Echeverry et al 2013;Ke et al 2013;Carpio et al 2015). Interestingly, a new study provided evidence to suggest that Bok is a noncanonical effector of MOMP in Bax/Bak DKO cells when its degradation is blocked by proteasome inhibition (Llambi et al 2016).…”
Section: Omm As the Direct Activator Of Bax/bak Following Neutralizatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis was not supported by the overwhelmingly strong apoptotic phenotype of Bax/Bak DKO cells (Wei et al 2001). Recent data from Bok knockout and Bax/ Bak/Bok triple-knockout cells further demonstrated that Bok's apoptotic activity is Bax/Bak-dependent and that it does not play a role as an effector protein during MOMP (Echeverry et al 2013;Ke et al 2013;Carpio et al 2015). Interestingly, a new study provided evidence to suggest that Bok is a noncanonical effector of MOMP in Bax/Bak DKO cells when its degradation is blocked by proteasome inhibition (Llambi et al 2016).…”
Section: Omm As the Direct Activator Of Bax/bak Following Neutralizatmentioning
confidence: 99%
“…Based on Bok's Bax/Bak-dependent apoptotic activity, it has also been suggested that Bok may function as a BH3-only protein (Echeverry et al 2013;Carpio et al 2015;). However, this proposition is in conflict with two important findings about Bok.…”
Section: Omm As the Direct Activator Of Bax/bak Following Neutralizatmentioning
confidence: 99%
“…For instance, through its own conserved BH3 domain, Bok might act itself like a BH3-only protein and directly activate Bax and Bak or neutralize anti-apoptotic Bcl-2 proteins, leading to BH3-only protein release, and Bax and Bak activation. In addition, Bok might form heterodimers with Bax and/or Bak, although previous studies failed to demonstrate a direct interaction of Bok with other multidomain proteins (Carpio et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…In line with this report, we also detected a certain portion of Bok not only at mitochondria, but also at the ER, as revealed by co-localization with the ER marker calnexin. It has been recently suggested that Bok might exert a selective role in ERstress-induced Bax and Bak activation, and promotion of mitochondrial apoptosis, as Bok −/− cells have been found to be defective in their response to ER stress stimuli (Carpio et al, 2015). The contribution of Bok to ER-stress-induced apoptosis, however, remains controversial, as other studies have detected no differences of Bok-deficient cells in their sensitivity to ER stress or have even reported that brefeldin-A-treated cells died faster in the absence of Bok (Fernandez-Marrero et al, 2016;Echeverry et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation